A contribution to the interpretation of Mt 5, 17-19 (Atti del Sodalizio Glottologico Milanese, 2014)
In this article an apparent contradiction regarding the Gospel will be treated. This is the idea that Jesus will complete the Torah, implying it is imperfect, while affirming at the same time that not a single iota will be changed, implying that it is perfect like that. It will be shown that there are indeed a number of observations that can lead us to the correct solution. In particular it will be discussed the semantic area of the Greek term πληρόω, ‘to complete’, but also ‘to fecundate, make fruitful’. KEYWORDS: semantics, Gospel, Greek, translation, lexicon